Prenatal diagnosis of auriculocondylar syndrome with a novel missense variant of GNAI3: a case report - Xiaoliang Liu; Wei Sun; Jun Wang; Guoming Chu; Rong He; Bijun Zhang; Yanyan Zhao (BMC, 2021)
Abstract Background Auriculocondylar syndrome (ACS) is a rare disorder characterized by micrognathia, mandibular condyle hypoplasia, and auricular abnormalities. Only 6 pathogenic variants of GNAI3 have been identified associated with ACS so far. Here, we report a case of prenatal genetic diagnosis of ACS carrying a novel GNAI3 variant. Case presentation A woman with 30 weeks of gestation was referred to genetic counseling for polyhydramnios and fetal craniofacial anomaly. Severe micrognathia and mandibular hypoplasia were identified on ultrasonography. The mandibular length was 2.4 cm, which was markedly smaller than the 95th percentile. The ears were low-set with no cleft or notching between the lobe and helix. The face was round with prominent cheeks. Whole-exome sequencing identified a novel de novo missense variant of c.140G > A in the GNAI3 gene. This mutation caused an amino acid substitution of p.Ser47Asn in the highly conserved G1 motif, which was predicted to impair the guanine nucleotide-binding function. All ACS cases with GNAI3 mutations were literature reviewed, revealing female-dominated severe cases and right-side-prone deformities. Conclusion Severe micrognathia and mandibular hypoplasia accompanied by polyhydramnios are prenatal indicators of ACS. We expanded the mutation spectrum of GNAI3 and summarized clinical features to promote awareness of ACS.